A preliminary survey of ectoparasites of small mammals in Pangkor Island, Perak, Malaysia - Farah Shafawati Mohd-Taib,; Asmalia Md. Lasim,; Rosha Asyikha,; Rahaniza Ali,; Siti Nabilah Ishak, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
Ectoparasite host a wide range of zoonotic pathogens and are significant source of disease that affected human and animals. However, little study has been conducted on island habitat. Pangkor Island is a virgin jungle reserve and one of the most popular tourist attraction located at Perak, Malaysia. This preliminary survey was conducted to determine the prevalence of ectoparasites on small mammals residing in this island’s forests. Small mammals were trapped by deploying 50 cage traps at two different sites which were Pangkor Selatan and Sg. Pinang forests. Ectoparasites were extracted from the captured individuals. Identification of the ectoparasite species was performed based on morphological features and molecular approach using COI (cytochrome oxidase subunit I) genes. A total of 13 individuals of small mammals belonging to 4 species (Maxomys surifer, Rattus tiomanicus, Maxomys rajah, Callosciurus notatus) were captured in the study areas. From these, 5 individuals from 2 small mammal species were infested with mites only, identified as Laelaps sp. The most infested host species was Maxomys rajah. Ectoparasites load in M. rajah was higher with 27 individual’s mites collected, compared to Rattus tiomanicus with 7. This study provides information on ectoparasites present on small mammal hosts within the study areas. Our findings suggest that the resident and tourist of the island area were exposed to mite bites and potentially infected by mite-borne disease, therefore, precaution should be taken to avoid contact with small mammal hosts by improving the cleanliness of the island.